TINGKAT KEPERCAYAAN DIRI MAHASISWA DITINJAU DARI PUBLIC SPEAKING - Sudarmono Sudarmono; Apuanor Apuanor; Eva Utami (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
This study aims to determine students' self-confidence. This research is conducted to know the confidence to express opinion in student discussion. Population in this research is all student of economic education program at STKIP Muhammadiyah Sampit which amounts to 298 students, which then taken 76 students as sample in this research. Data analysis technique used is scoring assisted by SPSS 15. The result of analysis shows that confidence convey the opinion in student discussion at STKIP Muhammadiyah Sampit Academic year 2016/2017 have confidence with medium category as much 38 students with 49.99% percentace.